Setting national nursing research priorities in Qatar: A Delphi survey - Albara Mohammad Ali Alomari; Kamaruddeen Mannethodi; Kalpana Singh; Jibin Kunjavara; George Vellaramcheril Joy; Ederlie Encarnacion Pitiquen; Badriya A. L. Lenjawi (Wiley, 2024)
Abstract Aim To establish consensus on the priorities of nursing research in Qatar regarding nursing administration, nursing practice and nursing education for the years 2023-2033. Design Classic Delphi format over three phases. Methods The first phase involved a qualitative round where participants identified 10 research priorities. In phase two, the collected sentences were analysed and grouped into themes. Participants were then requested to rate these sentences based on their perceived importance. During phase three, participants received their individual responses, the consolidated group response from the second round, and were given the opportunity to agree or disagree with the group ranking. The panel of experts consisted of 32 participants who agreed to participate in all three rounds. They included a mixture of nursing academics, clinical managers and nursing directors from public sectors and nursing schools in Qatar. Results The experts reached a consensus on the research priorities for Qatar. These prioritized topics focused on improving patient care outcomes, enhancing workforce development, strengthening nursing leadership, integrating technology to improve nursing and nursing education and promoting evidence‐based practice. Conclusion This research emphasizes the importance of progress in nursing to meet healthcare demands. Findings showed the need of future research to focus on improving nursing workforce and well‐being, leadership styles and technology, and evidence‐based practice and technology in nursing education. Impact The impact of identifying nursing research priorities in Qatar will improve healthcare practices, fostering a culture of evidence‐based care. These advancements will motivate nurses to engage more actively in research, thereby enhancing overall healthcare outcomes. Public Contribution Not applicable.